Properties of tire crumb and oil palm fruit fibre in lightweight mortar - Mohammed Bida, Sani (2014)
This research work was carried out to investigate the influence of oil palm fruit fibre (OPFF) in tire crumb incorporated mortar. It was necessitated due the increase in the quest for lightweight aggregate concrete which has been growing in recent years as a result of the benefit of reduced density of the self-weight of structural components derived from it. This has led the search for more suitable lightweight aggregate material that could be more suitable in terms of strength and durability. Attempt to use recycled waste tire as aggregate in concrete and mortar has been encouraging due to its low density when compared with natural mineral aggregates concrete. However, employing waste tire aggregates has always resulted in reduced strength properties such as compressive, flexural and tensile strengths. Most attempts made so far to recover the losses in strengths of waste tire concretes and mortars has been made by the use of chemicals, compounds or other additives to either pre-treat the waste tire aggregate surfaces or added to the matrix which may have a long time effect on the concrete material. These will increase cost of the mortar or concrete due to the cost of the chemical usage. Hence this research aims to use OPFF obtained as a by-product of the factory production of palm oil crude at 0.5%, 1% and 1.5% by mass of cement content and tire crumb aggregate content of 0%, 10%,20%, 30%, and 40% by volume of aggregate. Two types of tire crumb aggregates are included; untreated and treated using cement paste. The properties such as workability, density, absorption, compressive, split tensile, flexural strengths, shrinkage and microstructure were investigated. The result showed that for untreated tire crumb mortars, addition of OPFF at 0.5% by weight of cement improved these properties but with 1% and 1.5% OPFF, most of these properties reduce when compared to the control samples. On the other hand, these properties showed excellent performance in treated tire crumb mortars with an addition of 0.5 % -1.5% OPFF. In conclusion, the addition of OPFF in treated tire crumb (0-40%) mortars performed excellently at all fibre content (0.5-1.5%) and in untreated tire crumb of 0.5% OPFF content. Density of the mortar was also found to be decreased with increase in rubber and the addition of fibre did not affect the density significantly. However addition of OPFF showed significant effect on the durability such as water absorption of mixes regardless of the replacement percentages of tire crumb but affected by either treated or untreated tire crumb, with the treated tire crumb showed better results. Therefore, OPFF could be used in the development of structural lightweight mortar; however, more investigations are required to ascertain the durability performance of these composite mortar materials.